Pengaruh Kompetensi Profesional dan Kepribadian terhadap Kinerja Guru di SMAN 1 Sangatta Selatan - Erin Haerezky Alzizah; Eko Nursalim; Muh Ibnu Faruq Fauzi (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2026)
This study aims to determine the extent to which professional competence and personality competence influence teacher performance at SMAN 1 Sangatta Selatan. This research is categorized as field research using a quantitative approach. Data were collected through questionnaires to obtain responses from participants, observations to directly monitor activities, and documentation techniques to gather supporting data. The population in this study consisted of 33 teachers at SMAN 1 Sangatta Selatan. The sample was determined using the Slovin formula, resulting in 33 respondents, all of whom were teachers from the same school. To analyze the data, multiple linear regression analysis was employed. The results showed that professional competence significantly influences teacher performance. The influence of professional competence (X1) on teacher performance (Y) was 7.2%, while the influence of personality competence (X2) on teacher performance (Y) reached 4.5%. The coefficient of determination (R²) value was 0.807, indicating that 80.7% of teacher performance at SMAN 1 Sangatta Selatan is jointly influenced by professional competence (X1) and personality competence (X2), while the remaining 19.3% is influenced by other variables not examined in this study. Based on the analysis, personality competence was found to have a more significant simultaneous effect on teacher.